MiR-125b-5p ameliorates ventilator-induced lung injury in rats by suppressing ferroptosis via the regulation of the Keap1/Nrf2/GPX4 signaling pathway - Jiayi Zhang; Shuang He; Ke Wu; Yifan Wei; Chunyu Li; Qian Zhu; Siyu Lian; Li Wang; Fang Wan; Fuxiang Peng; Juan Zhang; Zongyu Chen; et al. (Scientific Reports)
Abstract Ventilator induced lung injury (VILI) is caused by improper use of mechanical ventilation, and its pathogenesis remains unclear. The aim of this study was to establish animal and cell models of VILI, and to explore the mechanism of miR-125b-5p in alleviating VILI by inhibiting ferroptosis through targeted regulation of Keap1/Nrf2/GPX4 axis. Firstly, ferrostain-1(Fer-1), a ferroptosis inhibitor, was used to confirm that ferroptosis was involved in the progression of VILI. Secondly, overexpression and knockdown of miR-125b-5p were performed to validate its function; Further, mechanistically, miR-125b-5p targets negatively regulated Keap1 to activate Nrf2 and then increased the expression of GPX4, thereby inhibiting the occurrence of ferroptosis. Finally, the rescue experiment shows, overexpression of Keap1 and use of the GPX4 inhibitor RSL3 reversed the miR-125b-5p effect, respectively. Through real-time quantitative polymerase chain reaction (qRT-PCR), western blotting (WB), immunofluorescence (IF), hematoxylin and eosin (H&E), and iron death related factor detection, it was confirmed that, overexpression of miR-125b-5p upregulates ferroptosis inhibitory protein and downregulates ferroptosis promoting protein, leading to alleviation of lung injury. However, overexpression of Keap1 and RSL3 reverses the effect of miR-125b-5p, respectively. Therefore, miR-125b-5p can inhibit ferroptosis and alleviate lung injury in VILI rats by targeting the Keap1/Nrf2/GPX4 axis, miR-125b-5p may be a potential intervention target for VILI.